Student teachers' prior knowledge as prerequisite to learn how to assess pupils' learning strategies. (November 2018) - Glogger-Frey, Inga; Deutscher, Marcus; Renkl, Alexander
Abstract: This study analyzed whether student teachers exhibit insufficient prior knowledge concerning learning strategies and whether different contexts lead to variations in activated knowledge. Furthermore, we investigated whether pieces of prior-knowledge and their structured-ness were associated with the assessment of pupils' learning strategies. In a within-subjects experiment (ABABAB design; N = 47 student teachers), questions about learning-strategy application referred to either (A) pupil-focused or (B) teacher-focused contexts. After a short training intervention, student teachers assessed strategies in pupils' work. Different prior knowledge was elicited depending on contexts, suggesting "knowledge-in-pieces". Prior-knowledge pieces, even if insufficient, served as a prerequisite to learn strategy assessment. Highlights: Student teachers' knowledge about learning strategies was misconceived and in pieces. Tailored short training prepared participants to assess strategies in student work. Correct conceptual knowledge on learning strategies predicted strategy assessment. Even misconceptual knowledge served as resource for learning to assess strategies.